Wheels of dreams and imagination: telling stories in a service of infant chemotherapy - Silmara de Oliveira Silva; Gilvânia Smith da Nóbrega Morais; Joseane Almeida Dias; Suzana Pereira Cardoso da Silva; Maria Smith Pereira; Mayra Shamara Silva Batista (Universidade Federal de Santa Maria, 2016)
Aim: to report the experience of Nursing students of telling stories to children in oncologic treatment. Methodology: this is a descriptive experience report, developed from the extension project: "Wheels of dreams and imagination: telling stories at a child outpatient in chemotherapy service", from May to December 2014, developed by the Federal University of Campina Grande (UFCG-PB), at a University Hospital. Results: through storytelling, it is possible to understand aspects related to the illness process experienced by the children and their family and, thereby, transform the practice of care and treatment. The study highlights the playful practices as the main approach tool among health professionals and the children's universe. Final Thoughts: the need for professionals to develop actions that come upon the status of being a child, not getting limited by projects that are developed in universities, is emphasized.